Verification of preventive measures - Tiganus, Georgiana-Alina (Eximia, 2023)
Preventive or restrictive measures of liberty and rights may be taken in criminal cases where there is reasonable suspicion that a crime punishable by imprisonment has been committed. It is worth noting that these preventive measures at this time can only be ordered if there is evidence or evidence from which to result the reasonable suspicion that a person has committed a crime, being necessary to achieve the goal pursued by taking them. During criminal proceedings, the competent judicial bodies have the authority to order certain procedural measures to ensure and guarantee the normal conduct of proceedings, the execution of the sentence, compensation for damage caused by the crime and the prevention of anti-social acts. Preventive, precautionary, safety and immediate redress measures, defined by doctrine as the return of property and restoration of previous condition, are examples of procedural measures that might be required during criminal proceedings. A verification phase of preventive measures is foreseen for the preliminary chamber proceedings and for the trial phase. This happens in terms of legality but also in terms of merits, from obtaining the file to the end of each procedural stage. The stage may end by revocation, substitution, legal termination or modification of obligations in the content of the judicial review, or by maintaining the preventive measure for the suspect if the conditions provided by law are met. Criminal judicial bodies may choose the preventive measure according to the criteria of Art. 218 para. 2 Code of Criminal Procedure. Preventive measures have a procedural nature and can only be taken if certain conditions provided by law are met, respecting a certain procedure and deadlines.